Rates of metastatic prostate cancer in newly diagnosed patients: Numbers needed to image according to risk level. Issue 12 (2nd June 2022) - Sorce, Gabriele; Hoeh, Benedikt; Flammia, Rocco S.; Chierigo, Francesco; Hohenhorst, Lukas; Panunzio, Andrea; Nimer, Nancy; Tian, Zhe; Gandaglia, Giorgio; Tilki, Derya; Terrone, Carlo; Gallucci, Michele; et al.
Abstract: Background: The numbers needed to image to identify pelvic lymph node and/or distant metastases in newly diagnosed prostate cancer (PCa) patients according to risk level are unknown. Methods: Relying on Surveillance, Epidemiology, and End Results (2010–2016), we tabulated rates and proportions of patients with (a) lymph node or (b) distant metastases according to National Comprehensive Cancer Network (NCCN) risk level and calculated the number needed to image (NNI) for both endpoints. Multivariable logistic regression analyses were performed. Results: Of 145, 939 newly diagnosed PCa patients assessable for analyses of pelvic lymph node metastases (cN1), 4559 (3.1%) harbored cN1 stage: 13 (0.02%), 18 (0.08%), 63 (0.3%), 512 (2.8%), and 3954 (14.9%) in low, intermediate favorable, intermediate unfavorable, high, and very high‐risk levels. These resulted in NNI of 4619, 1182, 319, 35, and 7, respectively. Of 181, 109 newly diagnosed PCa patients assessable for analyses of distant metastases (M1a–c ), 8920 (4.9%) harbored M1a–c stage: 50 (0.07%), 45 (0.1%), 161 (0.5%), 1290 (5.1%), and 7374 (22.0%) in low, intermediate favorable, intermediate unfavorable, high, and very high‐risk. These resulted in NNI of 1347, 602, 174, 20, and 5, respectively. Conclusions: Our observations perfectly validated the NCCN recommendations for imaging in newly diagnosed high and very high‐risk PCa patients. However, in unfavorable intermediate‐risk PCa patients, in whom bone and soft tissue imaging is recommended, the NNI might be somewhat elevated to support routine imaging in clinical practice.